Stress urinary incontinence in French elite women's rugby - Clapin, H.; Ramiz, L.; Raoul des Essarts, S.; Trandeau de Marsac, V.; Maître, C. (Science & Sports, 2025)
Background Stress urinary incontinence in elite sportswomen has been the subject of numerous studies, but few have focused on rugby despite being a high-risk sport with dynamic and isometric stresses on the perineum.